PERHITUNGAN PREMI TAHUNAN TIDAK KONSTAN DAN CADANGAN BENEFIT ASURANSI LAST SURVIVOR BERJANGKA - INTIHANIAH, HAFLATUL; WIDANA, I NYOMAN; JAYANEGARA, KETUT (E-Jurnal Matematika; Vol 12 No 2 (2023)DO - 10.24843/MTK.2023.v12.i02.p415, 2023)
Last survivor insurance is life insurance for two or more participants with premiums paid up to the death of the last participant. This study discusses term last survivor insurance for two participants, namely husband and wife. Compensation money is paid after the second person dies. The purpose of this study is to determine the value of annual premiums and benefit reserves in last survivor term insurance with non-constant premiums using a retrospective calculation method. The conclusion obtained for the annual premium model is not constant, the 10-year term last survivor insurance with an annual premium change of 10% of the fixed premium (  is that during the first 5 years, premiums with ? negative  are always greater than premiums with ? positive . But the opposite is true for the next 5 years. then, the value of reserves in the same year with ? negative is greater than ? positive, reserves with ? positive and ? negative also have the same pattern, namely increasing in the first year to the 6th year then decreasing in the 7th year until the contract expires.